IMPACT OF USING INTERACTIVE WHITEBOARDS (IWBs) ON STUDENTS’ ACHIEVEMENT AND RETENTION IN BIOLOGY IN SENIOR SECONDARY SCHOOLS IN ABUJA MUNICIPAL AREA COUNCIL, FEDERAL CAPITALTERRITORY, ABUJA - Egbunu , Roseline (Journal of Continuing and Development Education, 2024)
The study investigated the impact of using interactive whiteboards on students’ achievement and retention in Biology in senior secondary schools in Abuja Municipal Area Council, Federal Capital Territory, Abuja. Two research objectives, research questions and hypotheses guided the study. The study adopted descriptive survey research design. The population was made up of 1,646 respondents; comprising 38 Biology teachers and 1,608 SS III Biology students in all the eighteen (18) public senior secondary schools in Abuja Municipal Area Council. The sample size of 108 respondents comprising 90 Biology students and 18 Biology teachers and 9 senior secondary schools were adopted for the study. The sample size was selected using the combinations of purposive and simple random sampling techniques. Eight (8) items structured questionnaire titled “Interactive Whiteboards and Academic Achievement and Retention Questionnaire (IWAARQ)” was used as instrument for data collection. Content validity was used. Test-retest method of reliability was used to obtain the internal consistency. The reliability index was obtained through Cornbrash’s alpha (0.79). Data collected was imputed into the SPSS (25) software package. Mean score was used to answer the research questions and t-test was used to test the null hypotheses at 0.05 alpha level of significance. The results revealed among others that interactive whiteboards have positive impact on students’ achievement and retention in Biology in senior secondary schools. Inadequacy of interactive whiteboards and lack of power supply were constraints to the use of IWBs in senior secondary schools. It was recommended among others that government should equip the schools with adequate ICT media like interactive whiteboards, government should ensure stable power supply in all schools and Biology teachers should undergo training courses on ICT application in classroom instructional delivery.